The Use Of TPR Method In Teaching Vocabulary At Yayasan Al Falah - Sy, Evha Nazalatus Sa'adiyah; Chairunnisa (SELL (Scope of English Language Teaching, Linguistics, and Literature) Journal, 2023)
This research is to investigate how to apply the TPR method and the students’ response toward the implementation of this method at 6th grade MI an Al Falah Islamic education foundation. The data collected by using observation, interview and questioner. The result of the research of conducting TPR method to VI grade of described with descriptive qualitative method, the researcher uses saturation sampling methods in analyzing data, where all of number of populations become sample, there are one English teacher and 17 students. Based on the result of observation, interview and questioner has been finding that there are students’ response are faced by the teacher in applying of TPR method such as: the students like and enjoy the material, the students dislike this method and the students feel bored of conducting this method, beside that the researcher found the total numbers of students like this method for about 11 students, it shown when the teacher give a command and demonstrate the movement they respond it well, and 4 students dislike this method and 2 students feel bored of this method, it shown when the students cannot demonstrate the command of the teacher and they are not active in learning process.